Use of Echocardiography at Diagnosis and Detection of Acute Cardiac Disease in Youth with Systemic Lupus Erythematosus - Chang, Joyce C (Lupus, 2018)
OBJECTIVES: There are no guidelines on the use of echocardiography to detect cardiac manifestations of child-onset systemic lupus erythematosus (SLE). We quantify the prevalence of acute cardiac disease in youth with SLE, describe echocardiogram utilization at SLE diagnosis, and compare regional echocardiogram use with incident cardiac diagnoses. METHODS: Using the Clinformatics® DataMart (OptumInsight, Eden Prairie, MN) de-identified US administrative database from 2000–2013, we identified youth ages 5–24 years with new-onset SLE (≥3 ICD-9 SLE codes 710.0, >30 days apart) and determined the prevalence of diagnostic codes for pericardial disease, myocarditis, endocarditis and valvular insufficiency. Multiple logistic regression was used to identify factors associated with echocardiography during the baseline period, up to one year before or 6 months after SLE diagnosis. We calculated a regional echocardiogram utilization index, which is the ratio of observed use over the mean predicted probability based on all available baseline characteristics. Spearman’s rank correlation coefficient was used to evaluate the association between regional echocardiogram utilization indices and percent of imaged youth diagnosed with their first cardiac manifestation following echocardiography. RESULTS: Among 699 youth with new-onset SLE, 18% had ≥1 diagnosis code for acute cardiac disease, of which valvular insufficiency and pericarditis were most common. 25% of all youth underwent echocardiogram during the baseline period. Regional echocardiogram use was positively correlated with the percent of imaged youth found to have cardiac disease (ρ 0.71, p 0.05). There was up to a 5-fold difference in adjusted odds of baseline echocardiography between low and high-utilizing regions (OR 0.19, p 0.007). CONCLUSION: Nearly one-fifth of youth with new-onset SLE have acute cardiac manifestations, however use of echocardiograms at SLE diagnosis is highly variable. There may be incremental diagnostic value to early use of echocardiography, but prospective studies are needed to determine whether greater use of echocardiograms modifies outcomes.